2019
DOI: 10.4236/ojn.2019.92015
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Possibility of Virtual Reality in Nursing Skills Education: A Preliminary Study Using a First-Person Video

Abstract: Background: While demonstration videos from a third-person perspective have traditionally been used as teaching materials for nursing skills, first-person videos allow observers to experience how nursing educators move and what they see. In this pilot study, a first-person demonstration video for tracheostomy suctioning skills was shown to participants via a virtual reality (VR) head-mounted display (HMD), which we referred to as a VR teaching material (VR-TM). In an intervention experiment, we investigated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…At the same time, before virtual teaching, students need to increase the time of self-study before class to familiarize themselves with the virtual case, in order to complete the role task assignment and plan the operation time [ 20 , 21 ]. After class, one can also make an appointment in the laboratory to conduct rescue exercises of virtual cases again to consolidate first aid knowledge and skills [ 22 ]. The use of simulated humans in VR technology can repeatedly present rare or critical illnesses, allowing students to be exposed to more clinical cases within a limited time.…”
Section: Experiments and Analysismentioning
confidence: 99%
“…At the same time, before virtual teaching, students need to increase the time of self-study before class to familiarize themselves with the virtual case, in order to complete the role task assignment and plan the operation time [ 20 , 21 ]. After class, one can also make an appointment in the laboratory to conduct rescue exercises of virtual cases again to consolidate first aid knowledge and skills [ 22 ]. The use of simulated humans in VR technology can repeatedly present rare or critical illnesses, allowing students to be exposed to more clinical cases within a limited time.…”
Section: Experiments and Analysismentioning
confidence: 99%
“…In the studies, the first step in the teaching of skill is the patient character verification process [43,62,63]. In a thesis study conducted by Biyik Bayram [62], one of the process steps in the simulation scenario is the patient verification step.…”
Section: Identifying Patients Correctlymentioning
confidence: 99%
“…Koivisto et al [43], in their study with 166 nursing students, stated that students working with a simulation scenario were able to identify the descriptive characteristics of the patient and plan appropriate nursing interventions. Shibuy et al [63] in his study with 36 nursing students, it is expected that the student will verify the patient identity in the first step in the 24-item tracheostomy aspiration skill. As seen in the studies, nursing skills practices start with the verification step of the patient identity and the student must ensure the competence in simulation practice to fulfill this task in clinical practice (Table 1) [63].…”
Section: Identifying Patients Correctlymentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the use of VR in nursing student training on intravenous catheterization has been found to be a successful teaching tool [23]. An interventional study revealed that virtual reality (VR) instruction materials with first-person videos improved tracheal suction learning [22]. To perform urinary catheterization, a computer graphic-based VR system with haptic feedback was created [24].…”
Section: Introductionmentioning
confidence: 99%